2019
DOI: 10.1007/s12013-019-00888-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Initiation: a Discussion on Evidence for a “Load-Trigger” Mechanism

Abstract: Appropriate mechanical forces on cells are vital for normal cell behaviour and this review discusses the possibility that tumour initiation depends partly on the disruption of the normal physical architecture of the extracellular matrix (ECM) around a cell. The alterations that occur thence promote oncogene expression. Some questions, that are not answered with certainty by current consensus mechanisms of tumourigenesis, are elegantly explained by the triggering of tumours being a property of the physical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 140 publications
0
10
0
Order By: Relevance
“…All these examples point that phenotypes may become dominant over genotypes of the tumor cells depending on the microenvironment [1]. Thus, an altered mechanobiological profile of the cells and microenvironments (a mutationindependent element) is proposed to be necessary to promote development and spread of cancer [8]. However, there are no coherent quantitative data on the nature and level of mechanical forces that influence the interactions between the physical microand nano-environment and cancer cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…All these examples point that phenotypes may become dominant over genotypes of the tumor cells depending on the microenvironment [1]. Thus, an altered mechanobiological profile of the cells and microenvironments (a mutationindependent element) is proposed to be necessary to promote development and spread of cancer [8]. However, there are no coherent quantitative data on the nature and level of mechanical forces that influence the interactions between the physical microand nano-environment and cancer cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular environment also possesses physical and mechanical characteristics including stiffness, electrostatic charge, elasticity, compression and shear stress, which cooperate with a variety of biological factors and can affect a wide range of cellular behaviors [18][19][20]. Any disruption causing an imbalance in these biomechanical features can switch cell responses from normal to aberrant [21], although details are still unclear as to how cancer cells are affected by this balance. The fibrous constituents of the ECM, like collagen, along with physical characteristics like stiffness or elasticity, provide the ECM with topographical features that can generate a variety of biophysical and biomechanical cues, potentially dependent on size, dimension and type of topographies.…”
Section: Conceptualization Of Bioimprintingmentioning
confidence: 99%
“…It has been shown that interrupting aberrant ECM-to-cell signals mediated by integrins may normalize cell behavior and reverse tumor development (14). In addition, it was also suggested that the early development of ovarian cancer is dependent on potential tumor forming cells being bound to the sites in ovarian tissue with permissive, as distinct from tumor-inhibiting, characteristics (15). The commensurate inclusion of ARMs as a strategic component of a multi-targeted approach in larger clinical trials may therefore be warranted in ovarian cancer translation research.…”
Section: Dear Editormentioning
confidence: 99%